Teflon injection in the treatment of vesicoureteral reflux: A promising alternative for surgery - (:unkn) unknown (Kluwer Academic Publishers, 1991)
Vesicoureteral reflux is a common disorder of the urinary tract in children. The incidence is especially high in patients suffering from urinary tract infection. There is controversy in the management of the disorder and a recently introduced method, Teflon injection, seems to offer a promising alternative as a non-invasive technique. © 1991 Akadémiai Kiadó.